Chicago Classification Update (v4.0): Technical review on diagnostic criteria for hypercontractile esophagus. Issue 6 (17th March 2021) - Chen, Joan W.; Savarino, Edoardo; Smout, André; Xiao, Yinglian; de Bortoli, Nicola; Yadlapati, Rena; Cock, Charles
Abstract: Hypercontractile esophagus (HE), defined by the Chicago Classification version 3.0 (CCv3.0) as 20% or more hypercontractile peristalsis (Distal Contractile Integral >8000 mmHg·s·cm) on high‐resolution manometry (HRM), is a heterogeneous disorder with variable clinical presentations and natural course, leading to management challenges. An update on the diagnostic criteria for clinically relevant HE was needed. Literature on HE was extensively reviewed by the HE subgroup of the Chicago Classification version 4.0 (CCv4.0) Working Group and statements relating to the diagnosis of HE were ranked according to the RAND UCLA Appropriateness methodology by the Working Group, and the quality of evidence was rated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework. An overall emphasis of the CCv4.0 is on clinically relevant esophageal dysmotility, and thus it is recommended that an HE diagnosis requires both conclusive manometric diagnosis and clinically relevant symptoms of dysphagia and non‐cardiac chest pain. The Working Group also recognized the subtypes of HE, including single‐peaked, multi‐peaked contractions (Jackhammer esophagus), and hypercontractile lower esophageal sphincter. However, there are no compelling data currently for formally subdividing HE to these subgroups in clinical practice.